Creative Potential and Multicultural Experiences: The Mediating Role of Creative Self‐Efficacy. (19th April 2019) - Puente‐Diaz, Rogelio; Toptas, Seda Dilan; Cavazos‐Arroyo, Judith; Wimschneider, Christine; Brem, Alexander
Abstract: In two studies, one in Mexico and another one in Germany, we examined the indirect influence of self‐reported multicultural experience on creative potential, through its influence on creative self‐efficacy, and its direct influence on creative personal identity. In both studies, business students from Mexico and Germany completed a battery of questionnaires assessing creative self‐efficacy (with two different operationalizations), creative personal identity, multicultural experiences, and a divergent thinking task designed to generate ideas to solve two different business problems. Structural equation modeling was used to test our hypotheses. Results from both studies found a positive relationship between self‐reported multicultural experiences and creative personal identity. Similarly, multicultural experiences had an indirect, positive relationship with originality scores from a divergent thinking task, through its influence on creative self‐efficacy. Hence, the positive influence of multicultural experience on creative potential, through creative self‐efficacy, was established in two countries and with different operationalizations, trait like versus state like, of creative self‐efficacy. The implications of the results were discussed.